Observation of anharmonic coupling in the time domain with femtosecond stimulated Raman - Frontiera, R; Kukura, P; Mathies, R (Optical Society of America, 2006)
Coherent motion of low frequency bending vibrations is impulsively excited in CDCl3 and subsequent couplings between the C-D stretch and the low frequency coherences are detected in real time by femtosecond stimulated Raman spectroscopy (FSRS). © 2006 Optical Society of America.